(untitled) (Bangladesh Medical Journal, 2014)
This cross sectional study was carried out on 101 cases of vesico-vaginal fistula who were admitted and operated in Kumudini Women’s Medical College Hospital. The aim of the study was to find out the outcome of vesicovaginal fistula repair. A detailed interview was taken from the patients and attendants by using a questionnaire. Necessary information were collected from the patient’s record sheets . Small, medium and large sized fistulae were 59.41%, 26.73% and 11.88% respectively. The result of the study showed that success of fistula repair was 73.27%, though seven cases developed stress incontinence. Totally 27 patients were unsuccessfully repaired. Of which 19 (70.37%) were dropped out, 5(18.52%) were referred and 3(11.11%) had operative failure. Post-operative recovery was mostly (87.13%) uneventful. Urethral leakage (6.93%), blocked catheter ( 2.97%) and UTI (2.97%) were the leading complications. To improve the outcome, more training and skill of surgeons, improvised per-operative and post-operative care is necessary. Approaches should be designed to make the incidence of drop out to zero. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18652 Bangladesh Medical Journal 2011 Vol.40(3):18-20